A.L.KUN'S DATA AS A HISTORICAL SOURCE FOR THE STUDY OF THE HISTORY OF THE PEOPLES OF THE SOUTHERN ARAL SEA REGION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The Russian government's attempts to explore and study the Central Asian khanates began in the early 18th century, during the reign of Peter the Great, when the Khanate of Khiva became the object of Russia's close attention.